Pengaruh Periklanan, Harga dan Citra Merek terhadap Keputusan Pembelian Rokok Herbal PT. Tridaya Sinergi Indonesia: Survei pada Konsumen Rokok Herbal PT. Tridaya Sinergi Indonesia - Lutfi Alfiani; Budhi Wahyu Fitriadi; Depy Muhamad Pauzy (Pusat Riset dan Inovasi Nasional, 2024)
This study aims to determine the simultaneous and partial effect of Advertising, Price and Brand Image on Cigarette Purchase Decisions at Herbal PT. Tridaya Sinergi Indonesia. The research method used in this study is to use quantitative research methods. Respondents in this study were consumers of PT. Tridaya Sinergi Indonesia as many as 100 people. The type of data used in this study is primary data obtained through questionnaires. The data testing technique used in this study uses the validity test, reliability test and classic assumption test. Data analysis in this study used multiple regression analysis using SPSS software version 25. The results of the study show that advertising, price and brand image simultaneously have a significant effect on purchasing decisions. Advertising partially has a significant effect on the Purchase Decision. Price partially has a significant effect on purchasing decisions. Brand Image partially has a significant effect on Purchasing Decisions.